Measuring geospatial information system success on individual performance impact - Edie Kurniawan; Viany Utami Tjhin (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
This research will analyze the influence of the quality of sales IndiHome information system (SIIS) on individual performance. In this research, the SIIS dashboard quality aims to accommodate them using a model that meets the updated Delone and McLean model. Individual productivity is measured through the Net Individual Benefit variable. It measures the impacts obtained after using the SIIS dashboard on work success. Indihome is Telkom Indonesia broadband retail brand. In this business, the service must be installed for each house. The challenges are to provide the best service to customers, manage the chain of resources in a series of infrastructures for providing broadband services, and maintain business performance to be sustainable. Telkom Indonesia has developed a geospatial-based Sales Information System by utilizing geospatial and spatial analytics, so the data can be viewed comprehensively in one map. The interpretation of the SIIS dashboard shows that the success rate is at a high level for the six variables (system quality, user quality, information quality, information use, user satisfaction, and net individual benefit). There is also a significant effect in increasing the work productivity of SIIS dashboard users as indicated by the correlation measure between SIIS dashboard success and net individual benefits.